Pengaruh antara Followership, Kepuasan Kerja dan Loyalitas Karyawan terhadap Organizational Citizenship Behavior pada Karyawan CV. Mastha Medica - Lita, Kunnurul; Sumartik, Sumartik; Abadiyah, Rifdah (Universitas Islam Kadiri, 2024)
The role of human resources Managing an online business is very important to increase the rating and reputation of the shop. This can be supported by employees who have high Organizational Citizenship Behavior (OCB) so that they are able to carry out their roles well in the companyThis research aims to determine the influence of followership, job satisfaction and employee loyalty with Organizational Citizenship Behavior (OCB) on CV Mastha Medica Surabaya employees. Using quantitative methods as research design and using saturated sampling techniques as a technique in determining the sample size. Research object on CV. Mastha Medica Surabaya with 35 employees as respondents. Data was obtained by distributing questionnaires which were measured using a Likert scale which was then processed using the SEM-PLS method in the SmartPLS 3.0 application program. The results show that Followership has a positive and insignificant effect on Organizational Citizenship Behavior (OCB). The same results show that Job Satisfaction has a positive and insignificant effect on Organizational Citizenship Behavior (OCB). Meanwhile, the results show that employee loyalty has a positive and significant effect on Organizational Citizenship Behavior (OCB).